PENGARUH KEDISIPLINAN, PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BALAI BESAR WILAYAH SUNGAI BENGAWAN SOLO - Toto Wahono; Ida Aryati; Sri Hartono (ITB AAS INDONESIA Surakarta, 2019)
Concrete efforts that can support the improvement of the quality of professional performance of employees are training, motivation, and work discipline. These three factors are considered very decisive, because if they are observed and done well, it will have a positive impact on improving the quality of human resources or employee performance. The purpose of the study is to analyze the influence of discipline, training and work motivation simultaneously on employee performance of Big Hall Region Bengawan Solo River. Research is a descriptive study with a quantitative approach. The population of the study was all employees of the Central Bengawan Solo River Region of 600 employees, using Simple Random Sampling taken 25%, obtained a sample of 150 employees. The technique of collecting data using a questionnaire. The analysis tool uses multiple linear regression analysis. The results of linear regression analysis indicate that discipline, training and work motivation both partially and simultaneously have a significant positive effect on employee performance (p value